The link between dangerous driving and other criminal behaviour: a scoping review. Issue 2 (4th May 2022) - Bates, Lyndel; Alexander, Marina; Webster, Julianne
Abstract : Purpose: This paper aims to explore the link between dangerous driving and other criminal behaviour. Design/methodology/approach: Arksey and O'Malley's (2005) five-step process for scoping reviews to identify, summarise and classify identified literature was used. Within the 30-year timeframe (1990–2019), 12 studies met the inclusion criteria. Findings: This review indicates that individuals who commit certain driving offences are more likely to also have a general criminal history. In particular, driving under the influence, driving unlicensed and high-range speeding offences were associated with other forms of criminal behaviour. Seven of the studies mentioned common criminological theories; however, they were not integrated well in the analysis. No studies used explanatory psychosocial theories that investigate social and contextual factors. Research limitations/implications: Future research in this area would benefit from exploring individual and social influences that contribute to criminal behaviour in both contexts. Practical implications: There is the potential to develop an information-led policing approach to improve safety on the roads and reduce wider offending behaviour. However, it is critical that road policing officers continue to focus on ensuring the road system is as safe as possible for users. Originality/value: Criminal behaviour on the roads is often seen as a separate from other types of offending. This paper explores if, and how, these two types of offending are linked.